Anticorrosion composition, paint, coating and anode dog

CN119463554BActive Publication Date: 2026-10-27ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411615662.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2026-10-27
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

钢爪腐蚀不仅会缩短其使用寿命,形成“细腰”现象,且钢爪被腐蚀后形成的腐蚀物会进入电解质中,影响原铝的质量、电流的分布以及对电解槽运行工况的正确判断

Benefits of technology

[0020]本申请实施例提供的该防腐蚀组合物,所述防腐蚀组合物的原料包括:硬质粘土、高岭土、氟铝酸钾、六偏磷酸钠、硼砂、硅微粉以及石英砂;在所述防腐蚀组合物中,所述硬质粘土为55重量份~70重量份,所述高岭土为5重量份~15重量份,所述氟铝酸钾为5重量份~10重量份,所述六偏磷酸钠为5重量份~10重量份,所述硼砂为2重量份~8重量份,所述硅微粉为1重量份~6重量份,所述石英砂为1重量份~6重量份。硬质粘土的主要成分包括Al2O3和SiO2,并且具有致密的结构和均匀的质地,以及具有化学性质稳定和耐烧结的优势,可以有效阻挡高温气体与被保护基体的接触;高岭土具有良好的耐热性、可塑性以及分散性,从而可以改善防腐蚀组合物的高温塑性;氟铝酸钾和六偏磷酸钠中的碱金属离子,可以调节防腐蚀组合物的模数比,从而提高防腐蚀组合物的黏度和高温防腐蚀性能;硼砂在高温下会熔化并形成玻璃状物质,从而调节防腐蚀组合物在高温下的熔融状态,提高防腐蚀组合物的高温黏度;硅微粉和石英砂的主要成分为SiO2,可以调节该防腐蚀组合物的模数比,并且在高温环境下,SiO2促使基体表面会形成一层非常薄且致密的氧化膜,可以有效阻止氧气进一步向内部扩散,减缓氧化反应的进行,提高防腐蚀组合物的防高温气体腐蚀性能,以及硅微粉和石英砂可以协同调节粒度级配,充分填充涂料的空隙,从而提高防腐蚀组合物的强度;并且合理设计防腐蚀组合物中的各原料的含量,在高岭土、氟铝酸钾、六偏磷酸钠、硼砂、硅微粉以及石英砂的作用下,调整硬质粘土在高温下的塑性、熔点以及黏度等特性,从而更好地发挥硬质粘土的防高温气体腐蚀性能,进而提高了防腐蚀组合物的防高温气体腐蚀性能。因此,该防腐蚀组合物作为涂料的原料,可以提高该涂料的防高温气体腐蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463554B_ABST
    Figure CN119463554B_ABST
Patent Text Reader

Abstract

The application relates to an anticorrosion composition, paint, coating and anode steel claw, raw materials of the anticorrosion composition comprising hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon powder and quartz sand; in the anticorrosion composition, the hard clay is 55-70 parts by weight, the kaolin is 5-15 parts by weight, the potassium fluoroaluminate is 5-10 parts by weight, the sodium hexametaphosphate is 5-10 parts by weight, the borax is 2-8 parts by weight, the silicon powder is 1-6 parts by weight, and the quartz sand is 1-6 parts by weight. The anticorrosion composition provided by the application has excellent high-temperature gas corrosion resistance and thermal shock resistance, so that the anticorrosion composition as raw materials of paint can play a good protection role on the anode steel claw in aluminum electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating technology, and more particularly to an anti-corrosion composition, coating, coating layer and anode steel claw. Background Technology

[0002] The electrolytic aluminum anode consists of three parts: an aluminum conductor rod, steel claws, and prebaked carbon blocks. The steel claws connect the carbon blocks and the aluminum conductor rods, bearing the weight of the anode and transmitting a powerful current. At high temperatures of 400–900℃, the anode steel claws are susceptible to corrosion from the electrolyte, electrode feed material, air, and electrolytic flue gas. They also endure damage from thermal stress, electromagnetic forces, and impact forces, making them highly vulnerable to high-temperature oxidation and electrolyte corrosion. Steel claw corrosion not only shortens its service life and causes a "thin waist" phenomenon, but the corrosion products formed after the steel claws are corroded also enter the electrolyte, affecting the quality of the primary aluminum, the current distribution, and the accurate judgment of the electrolytic cell's operating conditions. Furthermore, steel claw corrosion increases the production cost of the anode steel claws to some extent.

[0003] Currently, corrosion protection for anode steel claws mainly includes protective ring technology, coating technology, and encapsulation technology. However, the protective effect of corrosion-resistant materials in coatings on anode steel claws is still not ideal. This is primarily because the use of anode steel claws involves a series of complex operations such as shell removal, material cutting, electrode replacement, and slag removal. Once the coating or protective ring on the anode steel claw cracks or falls off, it will lose its protective function. Therefore, reducing corrosion of anode steel claws is of great significance for extending their service life, improving the quality of primary aluminum, and reducing production costs. Summary of the Invention

[0004] This application provides an anti-corrosion composition, coating, coating layer, and anode steel claw to solve the following technical problem: how to improve the anti-corrosion performance of the anti-corrosion composition against high-temperature gas corrosion.

[0005] In a first aspect, this application provides an anti-corrosion composition, the raw materials of which include: anti-corrosion filler, the raw materials of which include: hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder and quartz sand;

[0006] In the corrosion-resistant composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silica powder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight.

[0007] Secondly, this application provides a coating material comprising the anti-corrosion composition described in any one of the first aspects.

[0008] Optionally, the weight of the anti-corrosion composition is 50% to 70% of the total weight of the raw materials of the coating.

[0009] Optionally, the raw materials for the coating may also include: catalysts, binders, emulsifiers, and additives.

[0010] Optionally, the adhesive includes inorganic adhesives and organic adhesives; and / or,

[0011] The catalyst comprises at least one of the following: yttrium oxide, titanium oxide, cerium oxide; and / or,

[0012] The emulsifier includes at least one of the following: vinyl acetate emulsion, acrylic emulsion, and polyurethane emulsion.

[0013] Optionally, the organic adhesive includes at least one of the following: epoxy resin, phenolic resin, furan resin; and / or,

[0014] The inorganic adhesive includes at least one of the following: silica sol, sodium silicate, and potassium silicate.

[0015] Optionally, the additives include at least one of the following: thickener, dispersant, defoamer, leveling agent, and high-temperature resistant metal-ceramic transition agent.

[0016] Optionally, in the coating, the anti-corrosion composition is 50 to 70 parts by weight, the catalyst is 2 to 6 parts by weight, the binder is 21 to 40 parts by weight, the emulsifier is 1 to 7 parts by weight, and the additives are 4 to 10 parts by weight.

[0017] Thirdly, this application provides a coating formed from the coating material described in any one of the second aspects.

[0018] Fourthly, this application provides an anode steel claw, the anode steel claw comprising an anode steel claw substrate and a coating as described in the third aspect attached to at least a portion of the surface of the anode steel claw substrate.

[0019] The technical solutions provided in this application have the following advantages compared with the prior art:

[0020] The anti-corrosion composition provided in this application embodiment comprises the following raw materials: hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder, and quartz sand; wherein, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silica powder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight. Hard clay, whose main components include Al2O3 and SiO2, possesses a dense structure and uniform texture, along with advantages such as chemical stability and resistance to sintering, effectively preventing high-temperature gases from contacting the protected matrix. Kaolin exhibits good heat resistance, plasticity, and dispersibility, thereby improving the high-temperature plasticity of the anti-corrosion composition. Alkali metal ions in potassium fluoroaluminate and sodium hexametaphosphate can adjust the modulus ratio of the anti-corrosion composition, thereby improving its viscosity and high-temperature anti-corrosion performance. Borax melts at high temperatures and forms a glassy substance, thus regulating the melting state of the anti-corrosion composition at high temperatures and increasing its high-temperature viscosity. Silica powder and quartz sand, whose main components are SiO2, can adjust the properties of the anti-corrosion composition. The modulus ratio is high, and under high-temperature conditions, SiO2 promotes the formation of a very thin and dense oxide film on the substrate surface, which can effectively prevent oxygen from further diffusing into the interior, slow down the oxidation reaction, and improve the high-temperature gas corrosion resistance of the anti-corrosion composition. Furthermore, silica powder and quartz sand can synergistically adjust the particle size distribution, fully filling the voids in the coating, thereby improving the strength of the anti-corrosion composition. The content of each raw material in the anti-corrosion composition is rationally designed; under the action of kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder, and quartz sand, the plasticity, melting point, and viscosity of hard clay at high temperatures are adjusted, thereby better utilizing the high-temperature gas corrosion resistance of the hard clay, and thus improving the high-temperature gas corrosion resistance of the anti-corrosion composition. Therefore, this anti-corrosion composition, as a raw material for coatings, can improve the high-temperature gas corrosion resistance of the coatings. Attached Figure Description

[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1This is a schematic flowchart illustrating a method for preparing a coating according to an embodiment of this application. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0025] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0026] In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this application, terms such as "comprising" and "including" mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Weight parts representation" such as parts by weight or parts by mass indicates the proportional relationship between components. In the proportional relationships discussed in this article, parameters that need to be described by proportion should be understood as the first term of the proportion in the order of description, while the proportion number should be understood as the second term. For example, if the weight ratio of substance A, substance B, and substance C is 1:2:3, then substances A, B, and C should correspond one-to-one with the proportion number in the proportion in the order of description, i.e., weight of substance A: weight of substance B: weight of substance C = 1:2:3.

[0027] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0028] In a first aspect, this application provides an anti-corrosion composition, the raw materials of which include: hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder and quartz sand;

[0029] In the corrosion-resistant composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silica powder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight.

[0030] In this embodiment, the hard clay is a refractory clay formed by deposition. The main components of the hard clay include Al2O3 and SiO2, and it possesses a dense structure and uniform texture, as well as advantages such as chemical stability and sintering resistance (refractory temperature greater than 1750℃), effectively preventing high-temperature gases from contacting the protected substrate. The hard clay can be 55 to 70 parts by weight, thereby fully realizing its resistance to high-temperature gas corrosion while avoiding the risk of cracking in the coating formed by the anti-corrosion composition due to the hard clay exceeding 70 parts by weight. For example, the hard clay can be 55 parts by weight, 57 parts by weight, 59 parts by weight, 61 parts by weight, 63 parts by weight, 65 parts by weight, 67 parts by weight, 69 parts by weight, 70 parts by weight, etc.

[0031] Kaolin's main components are Al4[Si4O] 10 Al(OH)8 is a hydrous aluminosilicate mineral belonging to the triclinic crystal system. Its crystal structure contains no cations or water molecules; the layers are connected by hydrogen bonds. It exhibits good heat resistance, plasticity, and dispersibility, and can improve the high-temperature plasticity of anti-corrosion compositions. Kaolin can be used in quantities of 5 to 15 parts by weight, thereby adjusting the Al / Si ratio in the overall anti-corrosion composition to ensure its reactivity and improve its high-temperature plasticity. For example, the kaolin can be used in quantities of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 parts by weight.

[0032] Potassium fluoroaluminate has high viscosity and strength, and the proportion of alkali metal cations in the anti-corrosion composition can be adjusted, thereby regulating the modulus ratio of the anti-corrosion composition. Potassium fluoroaluminate can be present in quantities of 5 to 10 parts by weight, effectively achieving the goal of adjusting the modulus ratio of the anti-corrosion composition and improving its high-temperature protective performance. The aforementioned modulus ratio represents the molar ratio of alkali metal to silica in the anti-corrosion composition, and this modulus ratio affects the high-temperature protective performance, hardness, plasticity, and chemical stability of the anti-corrosion composition. For example, the potassium fluoroaluminate can be present in quantities of 5, 6, 7, 8, 9, or 10 parts by weight.

[0033] Sodium hexametaphosphate has low viscosity and strength, but good solubility in water. This allows for adjustment of the alkali metal cation ratio in the corrosion-resistant composition. The sodium hexametaphosphate can be in the range of 5 to 10 parts by weight, effectively adjusting the modulus ratio and increasing the viscosity of the corrosion-resistant composition, thereby improving its high-temperature protective performance. For example, the sodium hexametaphosphate can be in the form of 5, 6, 7, 8, 9, or 10 parts by weight.

[0034] Borax melts at high temperatures and forms a glassy substance, thereby regulating the melting state of the coating at high temperatures and increasing its high-temperature viscosity. Borax can be used in quantities of 2 to 8 parts by weight, ensuring the anti-corrosion composition remains molten at high temperatures while preventing the coating from peeling off and failing at high temperatures if borax exceeds 8 parts by weight. For example, the borax can be used in quantities of 2, 3, 4, 5, 6, 7, or 8 parts by weight.

[0035] The main components of silica powder and quartz sand are SiO2, which can adjust the modulus ratio of the anti-corrosion composition. At high temperatures, SiO2 promotes the formation of a very thin and dense oxide film on the matrix surface, effectively preventing further oxygen diffusion and slowing down the oxidation reaction, thus improving the anti-corrosion composition's resistance to high-temperature gas corrosion. Silica powder has extremely fine particles, reaching submicron sizes, with high purity and good insulation. Quartz sand has larger particles, a wide particle size range, high hardness, and high mechanical strength. Therefore, silica powder and quartz sand can synergistically adjust the particle size distribution, fully filling the voids in the anti-corrosion composition, thereby improving its strength. The amount of silica powder can range from 1 part by weight to 6 parts by weight, and the amount of quartz sand can also range from 1 part by weight to 6 parts by weight, fully realizing the synergistic effect of silica powder and quartz sand in adjusting the particle size distribution, reducing the porosity of the anti-corrosion composition, and improving its strength. For example, the silica powder can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, etc., and the quartz sand can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, etc.

[0036] Therefore, by rationally designing the content of each raw material in the anti-corrosion composition, and by adjusting the plasticity, melting point, and viscosity of hard clay at high temperatures under the action of kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder, and quartz sand, the anti-corrosion performance of hard clay at high temperatures can be better utilized, thereby improving the anti-corrosion performance of the anti-corrosion composition.

[0037] Secondly, this application provides a coating material comprising the anti-corrosion composition described in any one of the first aspects.

[0038] In the embodiments of this application, the anti-corrosion composition is used as a raw material for coatings, which can improve the coating's resistance to high-temperature gas corrosion.

[0039] This coating is based on the above-mentioned anti-corrosion composition. The specific raw materials of the anti-corrosion composition can be referred to in the above embodiments. Since this coating adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.

[0040] In some embodiments, the weight of the anti-corrosion composition is 50% to 70% of the total weight of the raw materials of the coating.

[0041] In the embodiments of this application, the weight of the anti-corrosion composition can be 50% to 70% of the total weight of the raw materials of the coating, thereby fully realizing the anti-corrosion effect of the anti-corrosion composition against high-temperature gas corrosion. For example, the weight of the anti-corrosion composition can be 50%, 55%, 60%, 65%, 70%, etc., of the total weight of the raw materials of the coating.

[0042] In some embodiments, the raw materials of the coating also include: catalysts, binders, emulsifiers, and additives.

[0043] In some embodiments, the adhesive includes inorganic adhesives and organic adhesives; and / or,

[0044] The catalyst comprises at least one of the following: yttrium oxide, titanium oxide, cerium oxide; and / or,

[0045] The emulsifier includes at least one of the following: vinyl acetate emulsion, acrylic emulsion, and polyurethane emulsion.

[0046] In some embodiments, the organic adhesive comprises at least one of the following: epoxy resin, phenolic resin, furan resin; and / or,

[0047] The inorganic adhesive includes at least one of the following: silica sol, sodium silicate, and potassium silicate.

[0048] In this embodiment, the raw materials of the coating may further include: a catalyst, a binder, an emulsifier, and additives. The binder may include inorganic and organic binders. The synergistic effect of the organic and inorganic binders enables the coating to possess both good room temperature adhesion strength and excellent high-temperature adhesion strength. The organic binder may be one or more combinations of epoxy resin, phenolic resin, and furan resin; the inorganic binder may be one or more combinations of silica sol, sodium silicate, and potassium silicate. The weight ratio of inorganic binder to organic binder may be (18-35):(2-15), simultaneously ensuring excellent adhesion strength of the coating at both room temperature and high temperature. The organic binder decomposes and volatilizes under high temperature conditions without affecting the high-temperature performance of the coating. For example, the catalyst may be one or more combinations of yttrium oxide, titanium oxide, and cerium oxide, and the emulsifier may be one or more combinations of vinyl acetate emulsion, acrylic emulsion, and polyurethane emulsion.

[0049] In some embodiments, the additives include at least one of the following: thickener, dispersant, defoamer, leveling agent, and high-temperature resistant metal-ceramic transition agent.

[0050] In the embodiments of this application, the additives can be one or more combinations of thickeners, dispersants, defoamers, leveling agents, and high-temperature resistant metal-ceramic transition coatings. Thickeners are substances that increase the viscosity of fluids or semi-fluids, making them thicker; these thickeners can reduce the fluidity of coatings while increasing their viscosity. Dispersants are substances used to prevent the agglomeration of solid particles in liquids, ensuring uniform particle dispersion. Defoamers are substances used to eliminate or suppress foam generation in liquid systems. Leveling agents are additives that improve the leveling properties of coating materials such as paints and inks. High-temperature resistant metal-ceramic transition coatings can overcome the surface tension generated on the metal surface during coating application or seal small pores in the material, increasing coating adhesion.

[0051] In some embodiments, based on the total weight parts of the raw materials of the coating, the anti-corrosion composition is 50 to 70 parts by weight, the catalyst is 2 to 6 parts by weight, the binder is 21 to 40 parts by weight, the emulsifier is 1 to 7 parts by weight, and the additives are 4 to 10 parts by weight.

[0052] In the embodiments of this application, the anti-corrosion composition can be 50 parts by weight to 70 parts by weight, thereby fully realizing the anti-corrosion effect of the anti-corrosion composition against high-temperature gas corrosion. The catalyst can be 2 parts by weight to 6 parts by weight, thereby increasing the reactivity of the coating under high-temperature conditions and accelerating the reaction rate. The binder can be 21 parts by weight to 40 parts by weight, thereby enabling the coating to achieve a room-temperature bonding effect and undergo high-temperature solid-phase sintering. The emulsifier can be 1 part by weight to 7 parts by weight, thereby adjusting the state of the coating, changing the surface tension and permeability of the coating, and better wetting the substrate, thereby improving the adhesion of the coating. The additives can be 4 parts by weight to 10 parts by weight, thereby improving the thermal matching state between the coating and the steel claw, and reducing the risk of coating cracking caused by the difference in the coefficients of thermal expansion between the coating and the steel claw. For example, the anti-corrosion composition may be 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, etc.; the catalyst may be 2 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, etc.; the binder may be 21 parts by weight, 23 parts by weight, 26 parts by weight, 30 parts by weight, 33 parts by weight, 36 parts by weight, 40 parts by weight, etc.; the emulsifier may be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, etc.; and the additive may be 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, etc.

[0053] Figure 1 A schematic flowchart illustrating a method for preparing a coating provided in this application embodiment; please refer to [link / reference]. Figure 1The preparation method of the above coating includes: S1, mixing the anti-corrosion composition and the catalyst to obtain a first mixture; S2, mixing the binder, emulsifier and additives to obtain a second mixture; S3, mixing the first mixture and the second mixture to obtain the coating.

[0054] Thirdly, this application provides a coating formed from the coating material described in any one of the second aspects.

[0055] In the embodiments of this application, the coating can achieve good adhesion at room temperature, so that the coating is uniformly and densely adhered to the substrate surface to form a coating. The coating can be obtained by naturally curing the coating at room temperature for 2 hours.

[0056] The coating is based on the above-mentioned paint. The specific raw materials of the paint can be referred to in the above embodiments. Since the coating adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.

[0057] Fourthly, this application provides an anode steel claw, the anode steel claw comprising an anode steel claw substrate and a coating as described in the third aspect attached to at least a portion of the surface of the anode steel claw substrate.

[0058] In this embodiment, under high temperature conditions, the organic components in the coating volatilize, and the inorganic components undergo solid-phase sintering. Under aluminum electrolysis conditions, the hard clay in the coating reacts chemically with the electrolyte gas fluoride (sodium fluoride) to form a nepheline layer. The nepheline layer typically has a certain degree of density and hardness. This dense structure can prevent the penetration of oxygen and fluorinated gas, acting as a physical barrier. Nepheline has a certain degree of high-temperature stability, which can effectively block the oxidation of the steel claw material by high-temperature oxygen and the corrosion of the steel claw material by fluorinated gas, forming a good protective layer for the steel claw substrate, thereby improving the service life of the steel claw.

[0059] The anode steel claw is based on the above-mentioned coating. The specific coating material can be referred to in the above embodiments. Since the anode steel claw adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.

[0060] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0061] Example 1

[0062] A corrosion-resistant composition comprising: 62 parts by weight of hard clay, 12 parts by weight of kaolin, 6 parts by weight of potassium fluoroaluminate, 7 parts by weight of sodium hexametaphosphate, 5 parts by weight of borax, 4 parts by weight of silica powder, and 4 parts by weight of quartz sand, with a particle size of 0.5 μm-2 μm and a spherical shape.

[0063] A coating, comprising the following raw materials: 60 parts by weight of an anti-corrosion composition; 3 parts by weight of a catalyst, composed of titanium dioxide with a particle size of 0.1 μm-1 μm and a spherical morphology; 27 parts by weight of an inorganic binder, composed of 60 parts by weight of sodium silicate and 40 parts by weight of silica sol; 2 parts by weight of an organic binder, composed of phenolic resin; 2 parts by weight of an emulsifier, composed of acrylic emulsion; and 6 parts by weight of additives, comprising 5 parts by weight of a thickener, 5 parts by weight of a dispersant, 2 parts by weight of a pH adjuster, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 84 parts by weight of a high-temperature resistant metal-ceramic transition agent.

[0064] A method for preparing a coating includes: loading the raw materials and catalyst of an anti-corrosion composition into a three-dimensional mixer to mix the powder materials, with mixing parameters of frequency 35 Hz, rotation speed 20 r / min, and time 30 minutes, to obtain a first mixture; loading the binder, emulsifier, and additives into a magnetic heating stirrer to mix the liquid, with stirring parameters of rotation speed 40 r / min, temperature 70℃, and time 50 minutes, to obtain a second mixture; and uniformly mixing the first and second mixtures to obtain the coating.

[0065] Aluminum electrolytic anode steel claws: The surface of the aluminum electrolytic anode steel claws is pretreated to remove surface contaminants and obtain a clean surface. The coating is then applied to the steel claw surface by hand brushing and allowed to cure naturally at room temperature for 2 hours, resulting in a coating thickness of 1.6 mm. Under electrolytic conditions at 950℃, this coating forms an antioxidant and corrosion-resistant protective layer on the steel claw surface. This uniform and dense coating provides effective antioxidant protection, reducing the oxidation and corrosion rate of the steel claws from 2 mm / cycle to 0.3 mm / cycle.

[0066] Example 2

[0067] A corrosion-resistant composition comprising: 64 parts by weight of hard clay, 11 parts by weight of kaolin, 6 parts by weight of potassium fluoroaluminate, 6 parts by weight of sodium hexametaphosphate, 5 parts by weight of borax, 5 parts by weight of silica powder, and 3 parts by weight of quartz sand, with a particle size of 0.5 μm-2 μm and a spherical shape.

[0068] A coating, comprising the following raw materials: 58 parts by weight of an anti-corrosion composition; 2 parts by weight of a catalyst, composed of titanium dioxide with a particle size of 0.1 μm-1 μm and a spherical morphology; 28 parts by weight of an inorganic binder, composed of 70 parts by weight of sodium silicate and 30 parts by weight of potassium silicate; 4 parts by weight of an organic binder, composed of phenolic resin; 2 parts by weight of an emulsifier, composed of acrylic emulsion; and 6 parts by weight of additives, comprising 5 parts by weight of a thickener, 5 parts by weight of a dispersant, 2 parts by weight of a pH adjuster, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 84 parts by weight of a high-temperature resistant metal-ceramic transition agent.

[0069] A method for preparing a coating includes: loading the raw materials and catalyst of an anti-corrosion composition into a three-dimensional mixer to mix the powder materials, with mixing parameters of frequency 30 Hz, rotation speed 25 r / min, and time 25 minutes, to obtain a first mixture; loading the binder, emulsifier, and additives into a magnetic heating stirrer to mix the liquid, with stirring parameters of rotation speed 26 r / min, temperature 60°C, and time 40 minutes, to obtain a second mixture; and uniformly mixing the first and second mixtures to obtain the coating.

[0070] Aluminum electrolysis anode steel claw: The surface of the aluminum electrolysis anode steel claw is pretreated to remove surface contaminants and obtain a clean surface. Coating is then applied to the steel claw surface using pressure spraying and allowed to cure naturally at room temperature for 2 hours, resulting in a coating thickness of 0.8 mm. Under electrolysis conditions at 950℃, this coating forms an antioxidant and corrosion-resistant protective layer on the steel claw surface. This uniform and dense coating provides effective antioxidant protection, reducing the oxidation and corrosion rate of the steel claw from 2 mm / cycle to 0.5 mm / cycle.

[0071] Example 3

[0072] A corrosion-resistant composition comprising: 67 parts by weight of hard clay, 10 parts by weight of kaolin, 5 parts by weight of potassium fluoroaluminate, 6 parts by weight of sodium hexametaphosphate, 4 parts by weight of borax, 5 parts by weight of silica powder, and 3 parts by weight of quartz sand, with a particle size of 0.5 μm-2 μm and a spherical shape.

[0073] A coating, by weight, comprises: 56 parts by weight of an anti-corrosion composition; 3 parts by weight of a catalyst, which is composed of oxide, has a particle size of 0.1 μm-1 μm, and is spherical; 28 parts by weight of an inorganic binder, which consists of 20 parts by weight of sodium silicate, 30 parts by weight of potassium silicate, and 50 parts by weight of silica sol; 4 parts by weight of an organic binder, which is composed of furan resin; 3 parts by weight of an emulsifier, which is composed of vinyl acetate emulsion; and 6 parts by weight of additives, which consists of 3 parts by weight of a thickener, 3 parts by weight of a dispersant, 2 parts by weight of a pH adjuster, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 88 parts by weight of a high-temperature resistant metal-ceramic transition agent.

[0074] A method for preparing a coating includes: loading the raw materials and catalyst of an anti-corrosion composition into a three-dimensional mixer to mix the powder materials, with mixing parameters of frequency 30 Hz, rotation speed 25 r / min, and time 30 minutes, to obtain a first mixture; loading the binder, emulsifier, and additives into a magnetic heating stirrer to stir and mix the liquid, with stirring parameters of rotation speed 30 r / min, temperature 55℃, and time 35 minutes, to obtain a second mixture; and uniformly mixing the first mixture and the second mixture to obtain the coating.

[0075] Aluminum electrolysis anode steel claws: The surface of the aluminum electrolysis anode steel claws is pretreated to remove surface contaminants and obtain a clean surface. Coating is then applied to the steel claw surface using pressure spraying and allowed to cure naturally at room temperature for 2 hours, resulting in a coating thickness of 1 mm. Under electrolysis conditions at 950℃, this coating forms an antioxidant and corrosion-resistant protective layer on the steel claw surface. This uniform and dense coating provides effective antioxidant protection, reducing the oxidation and corrosion rate of the steel claws from 2 mm / cycle to 0.6 mm / cycle.

[0076] Example 4

[0077] A corrosion-resistant composition comprising: 58 parts by weight of hard clay, 12 parts by weight of kaolin, 8 parts by weight of potassium fluoroaluminate, 8 parts by weight of sodium hexametaphosphate, 4 parts by weight of borax, 5 parts by weight of silica powder, and 5 parts by weight of quartz sand, with a particle size of 0.5 μm-4 μm and a spherical shape.

[0078] A coating, comprising the following raw materials: 62 parts by weight of an anti-corrosion composition; 2 parts by weight of a catalyst, composed of cerium oxide with a particle size of 0.1 μm-1 μm and a spherical morphology; 28 parts by weight of an inorganic binder, composed of 20 parts by weight of sodium silicate, 30 parts by weight of potassium silicate, and 50 parts by weight of silica sol; 2 parts by weight of an organic binder, composed of furan resin; 2 parts by weight of an emulsifier, composed of polyurethane emulsion; 4 parts by weight of additives, composed of 4 parts by weight of a thickener, 4 parts by weight of a dispersant, 2 parts by weight of a pH adjuster, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 86 parts by weight of a high-temperature resistant metal-ceramic transition agent.

[0079] A method for preparing a coating includes: loading the raw materials and catalyst of an anti-corrosion composition into a three-dimensional mixer to mix the powder materials, with mixing parameters of frequency 40 Hz, rotation speed 25 r / min, and time 35 minutes, to obtain a first mixture; loading the binder, emulsifier, and additives into a magnetic heating stirrer to mix the liquid, with stirring parameters of rotation speed 35 r / min, temperature 55℃, and time 40 minutes, to obtain a second mixture; and uniformly mixing the first and second mixtures to obtain the coating.

[0080] Aluminum electrolysis anode steel claws: The surface of the aluminum electrolysis anode steel claws is pretreated to remove surface contaminants and obtain a clean surface. Coating is then applied to the steel claw surface using pressure spraying and allowed to cure naturally at room temperature for 2 hours, resulting in a coating thickness of 1 mm. Under electrolysis conditions at 950℃, this coating forms an antioxidant and corrosion-resistant protective layer on the steel claw surface. This uniform and dense coating provides effective antioxidant protection, reducing the oxidation and corrosion rate of the steel claws from 2 mm / cycle to 0.5 mm / cycle.

[0081] Comparative Example 1

[0082] Based on the disclosure in Example 1, Comparative Example 1 differs from Example 1 in that it contains 13 parts by weight of sodium hexametaphosphate and no potassium fluoroaluminate.

[0083] Under electrolytic conditions at 950℃, this coating can reduce the oxidation corrosion rate of steel claws from 2 mm / cycle to 1.8 mm / cycle.

[0084] Comparative Example 2

[0085] Based on the disclosure in Example 1, Comparative Example 2 differs from Example 1 in that it contains 50 parts by weight of hard clay and 24 parts by weight of kaolin.

[0086] Under electrolytic conditions at 950℃, this coating can reduce the oxidation corrosion rate of steel claws from 2 mm / cycle to 1.7 mm / cycle.

[0087] Comparative Example 3

[0088] Based on the disclosure in Example 1, Comparative Example 3 differs from Example 1 in that it contains 8 parts by weight of silicon micropowder and no quartz sand.

[0089] Under electrolytic conditions at 950℃, this coating can reduce the oxidation corrosion rate of steel claws from 2 mm / cycle to 1.8 mm / cycle.

[0090] Note: In Examples 1-4 and Comparative Examples 1-3 above, the thickener was Dayang Haiderun DH-02, the dispersant was Dayang Haiderun 5040, the pH adjuster was Dow AMP-95, the defoamer was tributyl phosphate type defoamer, the leveling agent was Dow RM-2020NPR, and the high-temperature resistant metal-ceramic transition agent was Zhisheng Weihua model ZS-1001.

[0091] As can be seen from Examples 1-4 and Comparative Examples 1-3, the coating of the anode steel claw provided in this application has an oxidation corrosion rate of less than 0.6 mm, which enables the coating to provide good protection for the anode steel claw in aluminum electrolysis.

[0092] One or more technical solutions in the embodiments of this application have at least the following technical effects or advantages:

[0093] (1) The coating provided in this application has excellent antioxidant properties and can effectively resist the oxidation of steel claws by high-temperature gases under aluminum electrolysis conditions, reducing the oxidation of steel claws by 90%.

[0094] (2) The coating provided in this application has excellent anti-corrosion properties and can form a nepheline layer with fluorides in high-temperature gas to prevent the corrosion of the anode steel claw by fluoride gas.

[0095] (3) The coating provided in this application has excellent thermal shock resistance. It has strong adhesion to the steel claw substrate under conditions of 500℃~900℃, and the coating does not crack or detach.

[0096] (4) The coating provided in this application embodiment can increase the service life of the anode steel claw by more than 2 times. It can not only reduce the Fe impurity content in the aluminum liquid, which is conducive to the production of high-quality primary aluminum products and increase the added value of the products, but also reduce the occurrence of the thin waist phenomenon of the steel claw, reduce the pressure drop of the steel claw, reduce the energy consumption of aluminum electrolysis, and reduce the production cost of enterprises.

[0097] (5) The coating provided in this application is simple to prepare, low in cost, and easy to industrialize. It can be applied by direct brushing or cold spraying. The process is simple and convenient. It has a positive significance for saving steel and reducing production costs in the aluminum electrolysis industry.

[0098] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A coating, wherein the raw materials of the coating include an anti-corrosion composition, the raw materials of the anti-corrosion composition comprising: Hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder, and quartz sand; In the corrosion-resistant composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silica powder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight. The weight of the anti-corrosion composition is 50% to 70% of the total weight of the raw materials of the coating; The raw materials for the coating also include: catalysts, binders, emulsifiers, and additives.

2. The coating according to claim 1, characterized in that, The adhesive includes inorganic adhesives and organic adhesives; and / or, The catalyst comprises at least one of the following: yttrium oxide, titanium oxide, cerium oxide; and / or, The emulsifier includes at least one of the following: vinyl acetate emulsion, acrylic emulsion, and polyurethane emulsion.

3. The coating according to claim 2, characterized in that, The organic adhesive includes at least one of the following: Epoxy resin, phenolic resin, furan resin; and / or, The inorganic adhesive includes at least one of the following: silica sol, sodium silicate, and potassium silicate.

4. The coating according to claim 1, characterized in that, The additives include at least one of the following: thickener, dispersant, defoamer, and leveling agent.

5. The coating according to claim 1, characterized in that, In the coating, the anti-corrosion composition is 50 to 70 parts by weight, the catalyst is 2 to 6 parts by weight, the binder is 21 to 40 parts by weight, the emulsifier is 1 to 7 parts by weight, and the additives are 4 to 10 parts by weight.

6. A coating formed from the coating according to any one of claims 1 to 5.

7. An anode steel claw, the anode steel claw comprising an anode steel claw substrate and a coating of claim 6 attached to at least a portion of the surface of the anode steel claw substrate.

Citation Information

Patent Citations

  • Coating material on fireproof material for continuous casting device and use method thereof

    CN103130521A

  • High temperature aluminium liquid corrosion resistant paint, and preparation method thereof

    CN109704577A

  • Organic-inorganic composite waterborne aluminum powder paint and preparation method thereof

    CN109868015A